Haunted dreams : fantasies of adolescence in post-Soviet culture - Kaminer, Jenny (Ithaca [New York] : Northern Illinois University Press, an imprint of Cornell University Press, 2022)
"This book analyzes representations of adolescence in Russian culture-including in prose, film, drama, and television-in the period since the end of the Soviet Union in 1991"--
The Ghost of Adolescence Past -- Adolescence as Nightmare -- Violent Imaginings -- Specters in the Schoolhouse.
Includes bibliographical references, filmography and index.
Description based on online resource; title from digital title page (viewed on March 09, 2022).
JSTOR
Keywords: Teenagers in mass media; Mass media and teenagers -- Russia (Federation); Teenagers -- Russia (Federation) -- Social conditions; Adolescents dans les médias.; Médias et adolescents -- Russie; Adolescents -- Russie -- Conditions sociales; Russia & the Former Soviet Union; Russian & Former Soviet Union; LITERARY CRITICISM; Drama; Europe; HISTORY; Mass media and teenagers; Teenagers in mass media; Teenagers -- Social conditions; Russia (Federation); Russia's adolescent turn, adolescence in Russia since 1991, protests against the regime of Vladimir Putin 2017, adolescent protagonist in literature, Russian tv show school, adolescent protagonist in television and film; Electronic books